2021
DOI: 10.1007/s40487-021-00146-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns and Outcomes Among Multiple Myeloma Patients with Asthma and COPD in the United States

Abstract: Introduction: Multiple myeloma (MM) is the second most frequent hematologic malignancy after lymphoma, contributing to approximately 10% of all hematologic malignancies. The prognosis of patients with MM is impacted by the heterogeneity of the disease, with worse outcomes reported in patients classified as International Staging System stage III, those with high-risk cytogenetics and elevated serum lactate dehydrogenase, and among patients who are elderly and have comorbidities. Previous studies have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A large Portuguese study has shown the odds of in-hospital mortality are lower in depressed patients, but the length of hospital stay is longer [37]. Similarly, in real-world data, overall survival from chronic obstructive pulmonary disease (COPD) in multiple myeloma is worse, which contradicts our finding of a low odds ratio of mortality in hospitalized patients [38,39]. The reason for these findings remains unclear.…”
Section: Predictors Of Aprdrg Disabilitycontrasting
confidence: 84%
“…A large Portuguese study has shown the odds of in-hospital mortality are lower in depressed patients, but the length of hospital stay is longer [37]. Similarly, in real-world data, overall survival from chronic obstructive pulmonary disease (COPD) in multiple myeloma is worse, which contradicts our finding of a low odds ratio of mortality in hospitalized patients [38,39]. The reason for these findings remains unclear.…”
Section: Predictors Of Aprdrg Disabilitycontrasting
confidence: 84%
“…Similarly, patients with MM presented with asthma or COPD showed significantly longer time from first- to second-line treatment. Additionally, the OS from first-line therapy was remarkably lower among patients with COPD, with a statistically significant decline in the OS from second-line therapy [ 32 ]. As no previous studies in the Middle East and North Africa region have provided the effect of first- or second-line treatment on patients with associated asthma or COPD, this study will assess the OS and PFS in those patients and compare the influence of first- or second-line therapy on survival.…”
Section: Discussionmentioning
confidence: 99%
“…And statistical analysis of clinical indicators showed that there was a significant difference in the expression of renal injury compared with the adverse prognosis of MM. The prognosis of MM patients is affected by many factors, such as international staging system, cytogenetic abnormality, underlying disease and age [ 32 ], studies have shown that IFI16 can be used as a biomarker for poor prognosis in MM [ 33 ]. Later, we will further follow up and monitor the survival and prognosis of MM patients.…”
Section: Discussionmentioning
confidence: 99%